SISTEM MANAJEMEN MUTU ISO 9001:2015 DI FAKULTAS EKONOMI, UNIVERSITAS NEGERI JAKARTA - Sagita, Destianty Noormala; Matin, Matin; Suryadi, Suryadi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2019)
Quality Assurance System is a management system to direct and control an organization/institution in determining policies, targets, plans and quality processes/procedures and their continuous achievement. The Faculty of Economics, Jakarta State University (FE-UNJ) is one of the institutions that has implemented the ISO 9001: 2015 standard in Higher Education striving to maintain and maintain the quality improvement consistency in all aspects. The 3 Main Components in Quality Management are: Quality Control, Quality Assurance, Quality Improvement. Management. Quality Management uses controls and guarantees for the product process to achieve quality more consistently. The basic pattern of quality management systems (ISO 9001: 2015) is what we will do and after we write (planning and reporting) and what we write we do is better known as the P-D-C-A pattern (Plan - Do - Check - Action). The concept of quality control is the basis for assessing the results to be achieved in the context of meeting customer needs and satisfaction.